Mercia : an Anglo-Saxon Kingdom in Europe. - Brown, Michelle P. (Continuum Collection., 2005)
The kingdom best remembered for Offa and his famous dyke was not only a dominant power on the island of Britain in the eighth century, but also a significant player in early medieval European politics and culture. Although the volume focuses on the eighth and ninth centuries when Mercian power was at its height, it also looks back to the origins of the kingdom and forward to the period of Viking settlement and West Saxon reconquest. With state-of-the-art contributions from experts in palaeography, art history, archaeology, numismatics and landscape - as well as from historians - this book esta.